From business perception to Public Policy: The construction of the ‘Sustainable Company’ Environmental Seal in the Municipality of Alegrete, State of Rio Grande do Sul (RS), Brazil (Research, Society and Development, 2025)
This article analyzes business perceptions regarding sustainability and environmental certification at the municipal level, based on a study conducted with 30 companies from different economic sectors in the municipality of Alegrete/RS. The study aimed to understand the level of knowledge, engagement, and willingness of the local productive sector in relation to sustainability practices and environmental certifications, supporting the formulation of Municipal Law No. 6,881/2025, which established the “Sustainable Company” Environmental Seal. The research, with a mixed-methods and applied nature, used a semi-structured questionnaire with 24 closed questions and one open question, combining quantitative and qualitative analysis. The results indicated that most companies adopt basic sustainability practices, such as waste separation and rational energy use, but lack technical knowledge and public incentives to advance in formal environmental certifications. Nevertheless, 82% of companies showed interest in joining the municipal seal, recognizing its relevance as an instrument of social value and competitiveness. It was found that business engagement can be enhanced by participatory public policies that recognize good practices and promote a culture of socio-environmental responsibility. The case of Alegrete reveals the potential of interaction between universities, public authorities, and the private sector in evidence-based policy formulation, constituting a replicable model of local environmental governance.